A study on dyslipidemia and its association with body mass index and smoking with or without chronic obstructive pulmonary disease among tribal population attending a teaching hospital in West Bengal state of India - Sarkar , Sumit; Gayen, Biplab Kumar; Biswas, Uttam; Dhua, Aparup; Swaika, Bikash Chandra; Das Bairagya, Tapan (Asian Journal of Medical Sciences, 2022)
Background: A large number of tribal populations reside in different parts of India. The indigenous population experiences a greater burden of diseases. Effects of tobacco smoking and smoking related disease such as chronic obstructive pulmonary disease (COPD) may be different among tribal populations. Aims and Objectives: This study was carried out to find out pattern of dyslipidemia and its association with body mass index (BMI) and smoking with or without COPD in tribal population. Materials and Methods: This cross-sectional and observational study carried out in a teaching hospital over a period of 1 year. All willing patients of both genders above 12 years of age belonging to any tribal community attended to hospital were included in this study. Demographic and anthropometric data along with reports of biochemical and other relevant tests were collected. SPSS version 27 was used for statistical analysis. Descriptive statistics and Chi-square tests were used. P≤0.05 was considered significant. Results: Among 190 patients, mean age of the study population was 46.3053±17.2563 (mean±standard deviation) years with male: female ratio of 4.94:1. About 14.7% patients were underweight, 66.3% patients were normal weight, 15.3% patients were overweight, and 3.7% patients were obese. Low high-density lipoprotein cholesterol was most common (47%) form of dyslipidema. No significant association found between dyslipidemia and BMI. 35.3% of patients were smoker. Association of BMI versus history of smoking was not statistically significant. Among smokers 29.9% patients had COPD. Association between COPD and history of smoking was statistically significant. Statistically significant association also found between with all component of lipid profile with smoking and COPD. Conclusion: Dyslipidemia is an important risk factor in ethnic tribal population. Smoking of tobacco is common among them. Smoking has significant association with all components of lipid profile. COPD has high prevalence among smokers of tribal community. COPD has significant association with all components of lipid profile among them.